2018
DOI: 10.1186/s12978-018-0659-4
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive health services utilization and its associated factors among adolescents in Debre Berhan town, Central Ethiopia: a community-based cross-sectional study

Abstract: BackgroundUtilization of reproductive health services is an important component in preventing adolescents from different sexual and reproductive health problems. As a result, the extent of their service utilization should be determined before implementing any kind of interventions. Therefore, this study was aimed at assessing the level of reproductive health services utilization and its associated factors among adolescents who live in Debre Berhan town.MethodsA community-based cross-sectional method was employ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
82
3
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(107 citation statements)
references
References 7 publications
11
82
3
1
Order By: Relevance
“…This nding is analogues with other studies elsewhere, which reported ever discussion on SRH issues was an independent predictor for SRH service utilization and showed adolescents who ever discussed on SRH issues with family were more likely to utilize SRH services than adolescents who did not discuss the issue with anyone else (1,5,27).Communicating SRH issues with parents is very crucial for adolescents so as to advance their awareness of SRH issues. Discussion of SRH issues with family members (especially if the family members have good knowledge on reproductive health problems and reproductive health services) increases adolescents' feeling of self-trust and there by urges their SRH seeking behavior.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This nding is analogues with other studies elsewhere, which reported ever discussion on SRH issues was an independent predictor for SRH service utilization and showed adolescents who ever discussed on SRH issues with family were more likely to utilize SRH services than adolescents who did not discuss the issue with anyone else (1,5,27).Communicating SRH issues with parents is very crucial for adolescents so as to advance their awareness of SRH issues. Discussion of SRH issues with family members (especially if the family members have good knowledge on reproductive health problems and reproductive health services) increases adolescents' feeling of self-trust and there by urges their SRH seeking behavior.…”
Section: Discussionsupporting
confidence: 87%
“…This could be also explained as with advancement of educational level; mothers are more likely to exchange SRH messages. In contrary, the studies conducted in Debre Berhan town and Woreta town showed no association between maternal education and adolescents' sexual and reproductive health services utilization (5,10). The variation can be emanated from cultural differences and religious beliefs towards SRH services used by adolescents.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The government of Nepal has termed young women as a vulnerable and underserved group to accomplish the speci c service required to meet their particular problems and needs. Independent studies conducted in Ethiopia [13,14], Bangladesh [15,16] and Nepal [17] have revealed that reproductive health service utilization among adolescent and youth was low and the use of reproductive health services was associated with different socio-demographic and economic factors. In Nepal, there are limited studies regarding the use of reproductive health services among young women.…”
Section: Introductionmentioning
confidence: 99%
“…Young people from sub-Saharan Africa countries are more at risk of sexual and reproductive health problems than those young people from around the world (10). The region remains the most affected region in the world with an estimate of 22.5 million people living with HIV and approximately 1.7 million new infections occurred in the region.…”
Section: Introductionmentioning
confidence: 99%